Effects of trunk extensor eccentric exercise on lipid profile and glycaemic response. Issue 1 (28th October 2020) - Lee, Ho-Seong; Akimoto, Takayuki; Kim, Ah-Ram
Abstract : Objectives: A number of previous studies reported physiological responses and adaptations after eccentric muscle contraction of limb muscles. In contrast, no study has determined physiological response after eccentric contraction of trunk muscles. The purpose of the present study was to compare the functional and metabolic changes after eccentric or concentric exercises of trunk extensor muscles. Methods: In this randomised, crossover study, 10 men performed a single bout of 50 maximal voluntary concentric and eccentric contractions of the trunk extensor with an interval of 2 weeks between bouts. The activities of the paraspinal muscles were recorded during concentric and eccentric contractions. Muscle soreness, muscle function, blood lipid profiles and glycaemic responses were measured before, immediately after and at 24, 48, 72 and 96 hours after each bout. Results: The lumbar multifidus and iliocostalis lumborum activities during eccentric contractions were significantly higher than those during concentric contractions (p<0.05). The maximal strength and muscle endurance of the trunk extensor were not decreased even after the eccentric contractions. Compared with concentric contractions, muscle soreness was significantly increased at 24, 48, 72 and 96 hours after eccentric contractions (p<0.05). The TG, TC and LDL-C were significantly lower at 48, 72 and 96 hours after eccentric contractions (p<0.05), while blood glucose levels and HOMA-IR were significantly greater at 48 and 72 hours after eccentric contractions (p<0.05). Conclusion: This study indicated that eccentric contractions of the trunk extensor had positive effects on the lipid profile and the glycaemic response.